Zambia Accelerator Program: Cohort 2 - Pele, Winnie (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Launched in February 2022, the science-driven AICCRA Zambia Accelerator Program offers a win-win solution for SMEs and investors alike - showing how science can be used to catalyze finance into climate-smart agriculture for meaningful change in businesses, through value chains, and with farmers and communities on the ground. AICCRA and partners have worked closely with the first cohort of 14 Zambian agribusinesses. Grouped into five innovation partnership bundles, each focused on scaling a combination of climate-smart agriculture (CSA) and climate information service (CIS) innovations in Zambia. With additional financing for the AICCRA project from the World Bank, AICCRA Zambia is launching another call for applications for a second cohort of the Accelerator grant. Under the Additional Financing (AF), there is an explicit effort to focus efforts on promoting access to~ and use of technologies and practices to reach 300,000 farmers, while further scaling along established impact pathways from 2024. To achieve these targets, the Accelerator program will contribute to de-risk private sector partners in scaling activities and identify suitable candidates through an open call for applications. The call for applications will be launched on the 19th of June and remain open until the 19th of July. Winners will be announced in August 2024. The proposed projects are anticipated to begin in September 2024 and continue until December 2025. Proposals must deliver a commercially sustainable business case for the involved partners that has the potential to run beyond the end of the project period.